2021
DOI: 10.3390/ani11030836
|View full text |Cite
|
Sign up to set email alerts
|

Seroconversion to Brucella spp. and Toxoplasma gondii in Sheep and Goats in Dohuk Province, Iraq and Its Association with Pregnancy Loss

Abstract: In this study, sera from 240 small ruminants (192 sheep and 48 goats) belonging to 12 farms in Dohuk Province, northern Iraq, were collected on two occasions to investigate the incidence risk of seroconversion to Brucella spp. and Toxoplasma gondii. All selected animals were confirmed pregnant (approximately 2 months pregnant) by ultrasound examination at the time of the first blood collection. A second ultrasound examination and blood sampling were undertaken two months after the initial scanning/sampling. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…A study conducted on pregnant ewes in Iraq found that ewes seroconverting to Brucella were 2.9 times more likely to lose their pregnancy than those remaining seronegative. In the same study, seroconverting to T. gondii had no significant impact on the loss of pregnancy [ 52 ]. Similarly, in another region of the world, only about 1.6% of lost lambs were attributed to T. gondii in a prospective cohort study in primiparous ewes from southern Australia, albeit at an overall much lower seroprevalence than in our study [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted on pregnant ewes in Iraq found that ewes seroconverting to Brucella were 2.9 times more likely to lose their pregnancy than those remaining seronegative. In the same study, seroconverting to T. gondii had no significant impact on the loss of pregnancy [ 52 ]. Similarly, in another region of the world, only about 1.6% of lost lambs were attributed to T. gondii in a prospective cohort study in primiparous ewes from southern Australia, albeit at an overall much lower seroprevalence than in our study [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…This analysis focused on impacts arising from loss of pregnancy and reduced milk yield, as these have been reported to be among the most significant outcomes of infection [ 11 , 27 ]. In this study, we populated the cost–benefit analysis model based on integrated data from our previous research on brucellosis in small ruminants in the study area; key model parameters were informed based on a recent cohort study [ 17 ] and a former cross-sectional serological survey carried out by our group in Dohuk [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inputs for the economic model ( Table 1 ) were sourced from: (i) a prospective cohort study conducted in Dohuk Governorate, where a sample of pregnant sheep flocks was followed over time to evaluate brucellosis incidence, seroconversion, and outcome of pregnancy [ 17 ]; (ii) a cross-sectional study conducted in Dohuk, which involved a serosurvey of sheep and goats from 72 farms [ 13 ]; and (iii) a questionnaire conducted on the same farms to gather information on production and prices. Where no data were available in the study area, input parameters were extracted from published literature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation